MENEMUKAN PEMEROLEHAN BAHASA KASAR PADA ANAK USIA 4 TAHUN DI KAMPUNG CIHANJAWAR PURWAKARTA - Utami, Resta Indriani Putri; Muslim, Faisal Latif; Supriatna, Enjang (IKIP Siliwangi, 2018)
This study aims to analyze the acquisition of crude language in children aged 4 years 1 month in Kampung Cihanjawar-Purwakarta, to obtain accurate results, need an accurate method of research as well. Data in this research using observation method with technique note then analyzed result from observation and conversation record conducted by child age 4 year 1 month then describe result of data and conclude result of data analysis. The results showed that there were three children who spoke abusively of children whose daily life was in poor language environment, then it can be concluded that the influence of the environment is very influential on the development of language. Based on these findings it can be concluded that children aged 4 years 1 month easily hear and reclaim the language absorbed from the surrounding environment.